The Effect of Liquidity, Profitability, and Dividend on Firm Value: Role of Capital Structure - Petronila, Thio Anastasia; Aprilianti, Angel (AJAR, 2024)
The aim of this research is to examine the effect of profitability, liquidity, and dividend policy on firm value with structure of capital as moderating variable. The research population, property, and real estate firms listed on the Indonesia Stock Exchange between 2018 and 2022. Purposive sampling combined with casewise diagnostics allowed for the selection of 101 observational data points for research samples. Descriptive statistics, multiple linear regression analysis, and moderated regression analysis were used for data analysis. Firm value is estimated by Tobin's Q ratio. The analysis results prove that profitability with return on assets shows a negative significant effect on firm value, liquidity with cash ratio does not affect firm value, and dividend policy with dividend pay-out ratio shows a positive significant effect on firm value. Structure of capital with debt on equity strengthens the effect of liquidity on firm value but does not moderate the effect of profitability and dividend policy on firm value.